2016
DOI: 10.1152/advan.00091.2015
|View full text |Cite
|
Sign up to set email alerts
|

Academic performance in human anatomy and physiology classes: a 2-yr study of academic motivation and grade expectation

Abstract: This project used a nonexperimental design with a convenience sample and studied the relationship between academic motivation, grade expectation, and academic performance in 1,210 students enrolled in undergraduate human anatomy and physiology (HAP) classes over a 2-yr period. A 42-item survey that included 28 items of the adapted academic motivation scale for HAP based on self-determination theory was administered in class during the first 3 wk of each semester. Students with higher grade point averages, who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 50 publications
3
35
1
3
Order By: Relevance
“…Their level of motivation to learn and their anticipation of the need for A&P knowledge in the future seem to be important for teachers' focus in future instructions. This finding is underlined by other research [4,5,17,20].…”
Section: Relationships Between Motivation and Independent Study And Pmentioning
confidence: 52%
See 1 more Smart Citation
“…Their level of motivation to learn and their anticipation of the need for A&P knowledge in the future seem to be important for teachers' focus in future instructions. This finding is underlined by other research [4,5,17,20].…”
Section: Relationships Between Motivation and Independent Study And Pmentioning
confidence: 52%
“…This was a self-reported survey, so answers may involve biases. The questionnaire was based mainly on instruments developed by Sturges et al [14] and Meehan-Andrews [20] and on their tests of validity and reliability. One weakness of the questionnaire was that it had only one question of motivation.…”
Section: Limitationsmentioning
confidence: 99%
“…Undergraduate human anatomy students reported that the quantity of material presented in the course was what prevented them from learning anatomy successfully (Wright 2012). Due to these perceptions and other factors, undergraduate anatomy and physiology courses may have high drop out, failure, and withdrawal (DFW) rates (Harris et al 2004, Sturges et al 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Ever since AMS was first developed in 1989, it has been used with all types of audience, including college students (Guay et al, 2015;Núñez Alonso et al, 2005) and in university courses, namely Business (Smith et al, 2010), Psychology (Cokley et al, 2001;Ramos, 2013), Physical Education (Spittle et al, 2009), Dentistry (Orsini, Evans, Binnie, Ledezma, & Fuentes, 2016), Physics, Mathematics and Nutrition (Lim & Chapman, 2015;Maurer et al, 2012;Sturges, Maurer, Allen, Gatch, & Shankar, 2016), among others, which gives us a clear indication this is a scale that can be adapted to any field of knowledge. In the case of the present research, it can be translated into Portuguese and specifically adapted to the Curricular Units (CUs) under survey.…”
Section: Development Interpretation and Validationmentioning
confidence: 99%